Effective Learning for Students with Autism: A Literature Review - Ediyanto, Ediyanto (The Center for Disability Studies and Services Brawijaya University, 2023)
The learning process requires the development of methods and media to support learning and increase students’ understanding and enthusiasm during the learning process. This literature review aims to identify effective learning methods for students with autism. The present study is essential to determine the development of effective learning methods for students with autism. In the end, this study concluded the presence of learning methods and media development for autistic students to increase interest and understanding during learning.